2023
DOI: 10.1002/cssc.202202289
|View full text |Cite
|
Sign up to set email alerts
|

Highly Coupled Heterobicycle‐Fused Porphyrin Dimers: Excitonic Coupling and Charge Separation with Coordinated Fullerene, C60

Abstract: Porphyrin dimers have been widely explored and studied owing to their importance in photosynthetic systems. A vast variety of dimers linked by different groups and at different angles have been synthesized and studied; however, the means by which to synthesize rigidly fused porphyrins with direct conjugation of the chromophores remains limited. Such a class of porphyrins may possess interesting properties that unconjugated or stacked dimers may not exhibit. In this study, bisbenzimidazolefused porphyrin dimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…10,33−39 For instance, Tian and coworkers have developed zinc porphyrin−viologen (ZnP−V) nanoparticles in an aqueous solution that showed a charge separation (CS) state lifetime of up to 4.3 ms. 30 This can be recognized as charge hopping induced by aggregation or distance modification between the donor and acceptor induced by electronic interaction. 31 D'Souza and coworkers 32 while transient absorption studies suggested that the lifetime of the final charge-separated state was in the 30−40 μs range. 32 Poddutoori and coworkers have reported a triad system in which a secondary donor bis-triphenylamino-boron-dipyrromethane (TPA 2 -BDP) was covalently connected to the axial position of Al(III) porphyrin (AlPorF 3 ), a primary donor and an acceptor pyridine appended naphthalenediimide (NDI) at another axial position, and observed a charge-separated state of (TAP 2 −BDP) •+ -AlP or F 3 −NDI •− .…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…10,33−39 For instance, Tian and coworkers have developed zinc porphyrin−viologen (ZnP−V) nanoparticles in an aqueous solution that showed a charge separation (CS) state lifetime of up to 4.3 ms. 30 This can be recognized as charge hopping induced by aggregation or distance modification between the donor and acceptor induced by electronic interaction. 31 D'Souza and coworkers 32 while transient absorption studies suggested that the lifetime of the final charge-separated state was in the 30−40 μs range. 32 Poddutoori and coworkers have reported a triad system in which a secondary donor bis-triphenylamino-boron-dipyrromethane (TPA 2 -BDP) was covalently connected to the axial position of Al(III) porphyrin (AlPorF 3 ), a primary donor and an acceptor pyridine appended naphthalenediimide (NDI) at another axial position, and observed a charge-separated state of (TAP 2 −BDP) •+ -AlP or F 3 −NDI •− .…”
Section: Introductionmentioning
confidence: 97%
“…31 D'Souza and coworkers 32 while transient absorption studies suggested that the lifetime of the final charge-separated state was in the 30−40 μs range. 32 Poddutoori and coworkers have reported a triad system in which a secondary donor bis-triphenylamino-boron-dipyrromethane (TPA 2 -BDP) was covalently connected to the axial position of Al(III) porphyrin (AlPorF 3 ), a primary donor and an acceptor pyridine appended naphthalenediimide (NDI) at another axial position, and observed a charge-separated state of (TAP 2 −BDP) •+ -AlP or F 3 −NDI •− . 10 Zhu et al developed two triads featuring fulleropyrrolidine−perylene tetracarboxylicdiimide−freebase porphyrin (FPP) and its zinc derivative (ZnFPP) for organic solar cells with a device efficiency of 0.35%.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations